Morphology and conservation of the Mesoamerican Slider (Trachemys venusta, Emydidae) from the Atrato river basin, Colombia (2014)
ABSTRACT:The phylogenetic relationships of the Mesoamerican Slider, Trachemys venusta, that inhabits the Atrato River basin of Colombia have been controversial as three different names have been proposed during the last 12 years: T. v. venusta, T. v. uhrigi, and T. ornate venusta. Using a group of sliders that was confiscated by the regional authority we compared the morphology of T. venusta distributed in the Atrato River with the morphology of the subspecies putatively distributed in Colombia. We found that the Colombian Mesoamerican slider has an overall smaller size, different plastral inter-scute seam formula, and different head, carapace and plastron coloration patterns. In addition, we also report the poor health condition of these individuals that have endured this illegal trade. We underscore an urgent need for further studies of individuals indigenous to Colombia to better understand the phylogenetic relationships of T. venusta throughout its distributional range, along with a more effective control of the illegal turtle trade in the Urabá region of Colombia.